Het huis van nu, waar de toekomst is : Een kleine historie van het Stedelijk Museum Amsterdam, 1895-1995. - Stedelijk Museum Amsterdam; Jansen van Galen, John; Schreurs, Huib (Naarden : V+K Publishing, 1995)
Grosz, George ; van Doesburg, Theo ; Chagall, Marc ; Klee, Paul ; van Dongen, Kees ; Werkman, Hendrik Nicolaas ; Beckmann, Max ; Malevich, Kasimir ; Pollock, Jackson ; Appel, Karel ; Ernst, Max ; Willink, Carel ; Koch, Pyke ; Sandberg, Willem ; Matisse, Henri ; Gestel, Leo ; Bacon, Francis ; Beuys, Joseph ; de Kooning, Willem ; Newman, Barnett ; Petersen, Ad ; Dubuffet, Jean ; Koons, Jeff ; Kuitca, Guillermo ; Perrotet, Vincent ; Paris-Clavel, Gérard ; de Maria, Walter ; Dumas, Marlene ; Daniels, René ; Birza, Rob ; Andriesse, Erik ; Lucebert ; Mondriaan, Piet ; Merz, Mario ; Judd, Donald
Nederlands
boek